An Analysis of Management Information Procedure in PT. Yamaha Tembung, Medan, Indonesia - Isnaniah LKS; Patar Marbun (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
In this study the authors describe the research with the title "An Analysis of Management Information Procedure in PT. Yamaha Tembung, Medan, Indonesia" at the Yamaha company. This study aims to determine whether the information management procedure system has met the elements of internal control in the company. The research method used is descriptive analysis method. The results of research conducted indicate that the overall system of information procedures applied to the company has fulfilled the elements of internal control that have been prepared well, but the elements of internal control in terms of good practice to satisfy consumers.